Activity of the Eyes bank at Santa Casa Hospital, Southern Brazil between 2003 and 2007 - Michelon, Veridiana Gobbi; Michelon, Tatiana; Garcia, Valter Duro; Marcon, Alexandre Seminotti (Brazilian Journal of Transplantation, 2009)
Purpose: To describe the cornea procurement at the Porto Alegre Santa Casa Hospital (CHSCPA), and to analyze its Eyes Bank (BOSCPA) activity between 2003 and 2007. Methods: Retrospective analysis of the cornea procurement at the CHSCPA and the medical records of internal and external donors assisted by BOSCPA during that period. There were applied t´Student test or Mann-Whitney, Qui-square and rates description by percentage, being significant P<0.05. Results: Among the 11398 deaths registered in the CHSCPA, 29.5% were potential donors and 10.6% of them became effective corneal donors. Medical contra-indication occurred in 51.9%, and familiar non-consentient for donation was 49.6%. The BOSCPA processed 3785 corneas from 2087 donors (62.7% internal and 37.3% external). The internal donors were older and dead due to neoplasia. The global refusal rate was 29% among processed tissues, being 64% of the corneas suitable for optical transplants and 36% for tectonical grafts. Conclusion: The CHSCPA had a relatively high familiar refusal and low potential donor rates, being its donors older and with malignant diseases. The BOSCPA, with more than 60% of its activity related to the internal donors, comprised 54% of the cornea procurement and 22% of the transplants performed in the state during this period.